Online flipped learning methods for teaching hospitality skills and management practices in an epidemic situation: A study on learning attitude and effectiveness - Chen, Kuo-Wei; Wang, Ze-Yung (Frontiers in Psychology, 2023)
The Covid-19 epidemic has been a pandemic for three years from 2019 to 2022. There seems to be no stopping trend. According to a UNESCO (United Nations Educational, Scientific and Cultural Organization) survey, more than 91% of students in the world have been affected by the spread of Covid-19. In Taiwan, although the application of technological networks can solve the problem of school suspension or online teaching which can effectively solve learning loss in the short term, Taiwan's higher education system is also facing a new and huge crisis. However, part of professional courses of the hospitality department, it is essentially impossible to accurately convey the color, aroma, and taste of the professional technology inheritance of hospitality, through online teaching. In addition, the level of each student varies greatly. During the online teaching process, the instructors teach the professional skills and movements through a single teaching video, which may not meet the needs of all students. Therefore, this study attempts to use the flipped teaching method. Try to make students can not only master the control of learning and effectively adjust their self-adaptive learning progress, but also help teachers solve problems and impart professional skills in a two-way interactive method through online teaching. It is believed that flipping a class using an online learning environment can effectively make up for the lacking of online video one-way teaching and the problem of poor online professional skill learning results. It can also induce students with poor learning attitude to actively participate in learning and improve the learning attitude of professional courses in hospitality. The results of this study found that in flipped classrooms using online learning environment, students' active learning effectiveness and learning attitude became positive, and their interest in learning and learning efficiency was also significantly improved. At the same time, it has stimulated the innovation, creativity, and creative development of students in the professional technology of hospitality to a certain extent, transformed the passive learning of online one-way teaching affected by Covid-19 into online two-way interactive teaching, and induced students to change from passive learning to active learning.